Comparison of Data Collection Methods: Advantages and Disadvantages - Kholifah, Eling Retno; Sofwan, Muhammad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This article aims to analyze the differences in data collection techniques in the research as well as identify the advantages and disadvantages of various methods, including surveys, interviews, observations, document analysis, experiments, and focus group discussions (FGDs). The research method used is a literature study, which involves tracing and analyzing written sources to understand the application of each technique. The results show that surveys offer efficiency and a wide range, but often neglect the depth of information needed to understand social contexts. Interviews and FGDs provide deeper insights, although they take time and can be influenced by researcher biases. Observation methods provide a good contextual understanding, but are subjective, while document analysis can present relevant historical data but must be critically evaluated. Experiments allow for the identification of clear cause-and-effect relationships, but are often carried out under artificial conditions that do not reflect reality. Taking into account technological developments, such as online surveys and mobile apps, this article concludes that a deep understanding of data collection techniques can help researchers design more effective and ethical research, resulting in findings that benefit society.